Perancangan Sistem Informasi Perpustakaan SMA N 1 Tengaran Menggunakan ROOT CAUSE ANALYSIS (RCA) - Arifuddin Mustofa; Christ Rudianto; Penidas Fiodinggo Tanaem (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
The lack of sophistication of schools utilizing information technology makes schools a little behind and less effective in lending services and book collection, because in service they still use a manual system, namely by writing in borrowed books, so an information system is needed that can assist in library services. The design of the library information system utilizes literature study analysis methods, observations, interviews and RCA (Root Cause Analysis) directly to students and librarians. RCA is also used as an analytical approach to a system design to understand an event in detail. This information system design documentation employs Unified Modeling Language (UML) modeling, namely use case diagrams, class diagrams, activity diagrams and sequence diagrams, it is hoped that the results of analysis and design can facilitate library services and increase the effectiveness of the lending process and book data collection.